STRATEGIES AND INNOVATIVE METHODS IN MODERN SCHOOL EDUCATION - Gaukhar Djanpeisova Erkinona (Web of Journals Publishing, 2025)
The content of a scientific article focused on developing in modern corresponding modern model of education and training of views on the development of mathematical concepts and abilities of children development of principles of section and design of the content of mathematical education of preschool children.
Keywords: Teaching and development of children; mathematical representations, innovative technologies; logical thinking; spatial orientation; game approaches